An integrated framework for non-destructive evaluation of bridges using UAS: a case study (2023)
The following paper proposes an Unmanned Aircraft System (drone) inspection framework for communities where guidelines for this emerging technology have yet to be provided. The framework involves pilot training in an area with similar features to the structure to be inspected, developing best inspection practices for future application, selecting a bridge for detailed inspection using non-destructive testing methods such as visual inspection, and inspecting the bridge using the UAS inspection framework developed for the area. The results of both reviews are compared, and the framework is validated. The fnal inspection framework is presented in the paper, along with relevant conclusions and future work. The proposed framework can be valuable for infrastructure owners and inspectors to conduct more efcient and cost-efective bridge inspections while ensuring safety in communities with limited UAS guidelines and research work. The structural analysis, qualitative assessment, and load rating of the case study are presented as proof of concept on the efectiveness of the UAS bridge inspection and its advantages.